E-Module for Preserving the Local Wisdom of Sidoarjo City among Generation Alpha in Elementary Schools - Norita Boru Sagala; M. Bambang Edi Siswanto; Nurul Istiq'faroh; Naffi Isbadrianingtyas (Academicus: Journal of Teaching and Learning, 2026)
The development of digital technology in the Society 5.0 era has had a major impact on the learning patterns of Generation Alpha in elementary schools. Generation Alpha is a group of children who grew up side by side with digital technology, thus requiring innovative, interactive, and contextual learning media. Therefore, teachers are required to be able to develop teaching modules that are adaptive to these technological developments. This study aims to develop an e-module containing the local wisdom of the traditional culinary "Klepon Sidoarjo" that is in accordance with the learning characteristics of Generation Alpha in the Indonesian Language subject of procedural text material in elementary schools. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 1 teacher and 25 fifth-grade students of SD Negeri Waru 1, Sidoarjo. Data collection instruments used included interviews, observations, and practicality response questionnaires. Based on the results of the student response questionnaire, an average score of 84% was obtained for usability, 80% for learning independence, and 82% for efficiency and technical fluency. Cumulatively, this Sidoarjo food e-module obtained a final average score of 82%. Referring to the media interpretation criteria, this score indicates that the e-module falls into the Very Practical category and is suitable for use as an interactive learning medium integrated with local wisdom for elementary school students in the digital era.